الثورة الفرنسية و المتغيرات الدولية (Comprehensive Journal of Science, 2025)
Modern international relations have contributed to helping nations avoid the horrors of war and destruction. The international relations that existed before various economic, political, and religious factors shaped 1789. The treaties and alliances formed among European nations primarily aimed to solve the conflicts and religious divisions that arose in Europe following the religious reform movements.One of the most significant and impactful changes in modern international relations during the late 18th and early 19th centuries was the French Revolution and the new ideas it generated, which prepared the world to adopt a revolutionary mindset and demonstrated a willingness to abolish old systems. As a result, treaties and alliances established after 1789 included provisions primarily aimed at limiting the intellectual and political reach of France.